2015
DOI: 10.1093/abbs/gmv096
|View full text |Cite
|
Sign up to set email alerts
|

Changes of intracellular Ca<sup>2+</sup> in quercetin-induced autophagy progression

Abstract: Quercetin was previously reported to exhibit significant anti-proliferative activities, and its major effect on tumors was to induce cell apoptosis or autophagy. However, the specific mechanism remains controversial. In this study, autophagy induced by quercetin was determined with various methods. Intracellular Ca 2+ ([Ca 2+ ] i ) was measured after being incubated with Fluo-3 acetoxymethyl (AM). At the same time, the relationship between the intracellular Ca 2+ and autophagy induced by quercetin was further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In addition, LRRK2 overexpression upregulates the levels of SQSTM1/p62 in a Ca 2+ -dependent manner, which links ubiquitinated targets to the autophagic machinery [72]. Finally, a recent study inferred that quercetin could induce autophagy and is attributed to the elevated Ca 2+ , although the specific mechanisms of the calcium-signaling pathway in quercetin-induced autophagy remain to be revealed [73]. …”
Section: Induction Of Autophagy By Ca2+mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, LRRK2 overexpression upregulates the levels of SQSTM1/p62 in a Ca 2+ -dependent manner, which links ubiquitinated targets to the autophagic machinery [72]. Finally, a recent study inferred that quercetin could induce autophagy and is attributed to the elevated Ca 2+ , although the specific mechanisms of the calcium-signaling pathway in quercetin-induced autophagy remain to be revealed [73]. …”
Section: Induction Of Autophagy By Ca2+mentioning
confidence: 99%
“…The differences between autophagy and apoptosis induction were also mentioned with regard to thapsigargin, ionomycin, and vitamin D3 [25]. However, different from cadmium-induced cytotoxicity, the induction of autophagy by quercetin manifests a protective effect by inhibiting apoptosis, attenuating lipid peroxidation, and recovering mitochondrial function [73]. Furthermore, recent evidence has shown that cells undergo autophagy instead of apoptosis if Bax/Bak is knocked out after hypericin-PDT treatment, which leads to ER Ca 2+ depletion, although whether this phenomenon arises from the destruction of Ca 2+ homeostasis or the subsequent ER stress was not investigated [51].…”
Section: Ca2+ Connection In Autophagy and Apoptosismentioning
confidence: 99%
“…By inhibiting the PI3K/Akt pathway quercetin also inhibits proliferation of HeLa cells and breast carcinoma cell lines and induces apoptosis in promyelocytic HL-60 cells [39][40][41]. In HepG2 hepatocellular carcinoma cells quercetin was found to mediate autophagy by release of Ca 2+ from intracellular stores [42] and to enhance apoptosis by induction of a positive feedback loop consisting of p53, miR-34a miRNA and SIRT1 [43]. The present study was performed to investigate short and long-term effects of quercetin and rutin on beta-cells [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…calcium-transporting ATPase under quercetin treatment in A. flavus (Tiwari and Shankar 2018 ). The effect of quercetin on Ca +2 concentration has also been studied using HepG2 cells (Cui et al 2015 ) that showed an increase in calcium ion concentration inside the cells and the flow of calcium ions among cell organelles. Whereas in case of breast cell cancer quercetin suggested to induce apoptosis in MDA-MB-231 cells by a reduction in calcium dependent urokinase which leads to decrease in intracellular calcium uptake in cells (Devipriya et al 2006 ).…”
Section: Resultsmentioning
confidence: 99%